USABILITY ANALYSIS OF INDUSTRIAL PRACTICE INFORMATION SYSTEM (SIPI) USING SYSTEM USABILITY SCALE (SUS) IN INFORMATICS AND COMPUTER ENGINEERING DEPARTMENT UNM - Andini Wulandari; Muhammad Yusuf Mappeasse; Shabrina Syntha Dewi; Firdaus Firdaus (Jurnal Media Elektrik, 2025)
This study aims to analyze the level of usability in the Industrial Practice Information System (SIPI) using the System Usability Scale (SUS) method in the Informatics and Computer Engineering Department, UNM. This research is a type of quantitative descriptive research, the data collection techniques used are questionnaires, interviews and documentation. The subjects of this study were students of the Informatics and Computer Engineering Department, class of 2021, who were taken using nonprobability sampling using the saturated sampling method totaling 60 people. The difference between this study and several previous studies is in the method used and the determination of the SUS score, which is not only from 3 aspects, namely acceptability, grade scale, adjective rating, but also with percentile rank and analysis of respondent responses. From the results of the analysis, it was found that the level of usability in the Industrial Practice Information System (SIPI) using the System Usability Scale (SUS) method, namely the SUS score of 60 with a percentile rank value of 29%, with a grade scale that falls into the category "D", for the adjective rating is in the category "Ok" which means that the usability of SIPI is quite decent. Furthermore, the acceptability ranges aspect is in the category "Marginal" which means that SIPI can be marginally accepted/can be accepted with conditions by users. From the results of the analysis of user responses to the SUS questionnaire, it is known that the usability aspects that still have a low percentage value are the memorability and learnability aspects. Thus, SIPI can be accepted by users however, improvements or developments are still needed to optimize the use of the system, especially in the usability aspect which has a low percentage value, namely memorability and learnability.